Fine coal beneficiation by column flotation - Han, O.; Kim, M.; Kim, B.; Subasinghe, Nimal; Park, Chul hyun (Elsevier, 2014)
The amenability of beneficiating a fine hard coal from Hwa-Sun coal mine using column flotation has been studied using a CoalPro flotation column developed by Canadian Process Technologies (CPT). After initial testwork using a batch flotation cell to determine the optimal flotation conditions, tests were carried out to compare its performance with the column. The results showed that the performance of the column was far superior to that of the conventional cell owing to the large fines content present in the coal. It was established that a stable froth column of 40 cm in height and a suitable balance between froth and collection zone could be maintained at 1.0 cm/s superficial gas rate. A suitable reagent scheme and the optimal operating conditions that minimized adverse effects generally encountered in treating fine coal, such as gangue entrainment, have been identified. An increase in water recovery significantly decreased ash rejection implying entrainment of fine ash particles. Column flotation is capable of producing an acceptable clean coal concentrate of 85% combustible recovery with 81% ash rejection at a maximum separation efficiency of 62%, compared to conventional flotation which has 70% recovery with 70% ash rejection at an efficiency of 42%.